Pseudomonoballismus in a Deafferented Arm Following Combined Medullary and Cerebellar Lesions of the Proprioceptive Pathways. Issue 3 (11th August 2016) - McGovern, Eavan M.; Foley, Maurice; Looby, Seamus; Connolly, Sean; Farrell, Michael; Healy, Daniel G.
Abstract : View Supplementary Video 1